A Convenient One-pot Synthesis of 2,3-Disubstituted Thieno[2,3-d]pyrimidin-4(3H)-ones from 2H-Thieno[2,3-d][1,3]oxazine-2,4(1H)-diones, Aromatic Aldehydes and Amines - Liu, Feize; Hou, Xueling; Nie, Li Fei; Bozorov, Khurshed; Decker, Michael; Huang, Guozheng (SynOpen, 2018)
An efficient, simple protocol has been established for convenient synthesis of novel 2,3-disubstituted thieno[2,3-d]pyrimidin-4(3H)-one derivatives in good to high yields through a one-pot, two-step and three-component reaction from 2H-thieno[2,3-d][1,3]oxazine-2,4(1H)-diones, aromatic aldehydes, and amines.
Keywords: thieno[2,3-d]pyrimidin-4(3H)-one; one-pot synthesis; intramolecular cyclization; pyrimidinone; quinazolinone